The role of educational institutions in preserving the Malay language: Insights from the Patani ethnic community in southern Thailand - Yunariono, Bastian (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
For over a century, the Thai government's assimilationist policies have hindered the development of the Patani people’s cultural identity, which blends Malay and Islamic cultures. These cultural impediment is reflected in the language as the Patani have experienced a decline in their ability to use the Malay language as a marker of their identity. This study aims to explain the role of educational institutions such as Islamic boarding schools (pesantren), private Islamic schools (madrasah), and kindergartens (tadika) in preserving the Malay language. This study employed a qualitative research method, utilizing library resources such as journals, books, reports, and websites. The results indicated that these educational institutions play a significant role in preserving the Malay language among the Patani. By using Malay as a means of communication and as a subject of study in these educational institutions, the Patani ethnic identity can be preserved.